Transformational Leadership and Job Satisfaction: Unveiling the Roles of Contingent Reward and Affective Commitment (KASBIT Business Journal, 2026)
This research examines how transformational leadership affects employee job satisfaction while considering the mediating influence of affective commitment and the moderating influence of contingent reward. Research data focuses on the banking sector and was collected through a cross-sectional survey. The explanatory study utilized questionnaires and was implemented on a sample of 340 employees of the surveyed banks. The research conducted correlational analysis and utilized Partial Least Squares (PLS) Structural Equation Modeling (SEM) analysis. Findings indicate that transformational leadership positively affects employee job satisfaction while contingent reward modifies this relationship. Affective commitment partially meditated the transformational leadership-job satisfaction relationship. This study seeks to fill the gap in the literature by recognizing affective commitment and contingent reward contributing the impact as mediating and moderating variables respectively in the interplay of transformational leadership and employee job satisfaction. The foundational theories of the study are Transformational Leadership Theory and Full Range Leadership Theory (FRLT). The study develops on leadership practices in the banking sector and proposes actionable strategies to improve employee job satisfaction.